Big Red and the Little Bitty Wolf : a story about bullying - Ransom, Jeanie Franz, 1957-; Zivoin, Jennifer (Washington, DC : Magination Press/American Psychological Association, 2016)
Big Red Riding Hood has been bullying Little Bitty Wolf since she moved into the neighborhood and his parents' advice does not help, but their school counselor, Mr. Know-It-Owl, makes a comment that just might set things right.
Ages 4-8.
Keywords: Bullying -- Fiction; Wolves -- Fiction; Characters in literature -- Fiction; Bullying -- Juvenile fiction; Wolves -- Juvenile fiction; Characters in literature -- Juvenile fiction; Little Red Riding Hood (Tale) -- Adaptations